Optimising patient fitness: strategies to reduce the effects of cancer cachexia in patients with advanced lung cancer. Issue 4 (December 2020) - Phillips, Iain; Kestenbaum, Samantha
Abstract : Purpose of review: Outcomes for patients with advanced lung cancer have traditionally been very poor. This patient group are often comorbid, less fit and experience multiple symptoms. This review discusses strategies for minimizing the impact of cachexia on patients with advanced lung cancer. This is timely, as in recent years there has been a rapid increase in available systemic therapy options, with the potential of long-term survival for some patients. Recent findings: The review discusses current strategies in combating cachexia, including: symptom control, systemic therapy for cancer and for cachexia, nutritional interventions and exercise interventions. It discusses current clinical trials, combining interventions and the paradigm of prehabilitation. Summary: It is likely that the optimal way of minimizing the impact of cachexia in advanced lung cancer is through a combination of early interventions including symptom management.